2012
DOI: 10.4161/hv.18432
|View full text |Cite
|
Sign up to set email alerts
|

Safety, immunogenicity and efficacy of pneumococcal conjugate vaccine in HIV-infected individuals

Abstract: Streptococcus pneumoniae is the leading bacterial opportunistic infection in HIV-infected individuals. Anti-retroviral treatment (ART) of HIV-infected individuals reduces their risk of invasive pneumococcal disease (IPD), however, it remains 20- to 40-fold greater compared with age-matched general population. This review summarizes the available published data on the immunogenicity, safety and efficacy of pneumococcal polysaccharide-protein conjugate vaccines (PCV) in HIV-infected children and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 83 publications
(193 reference statements)
1
41
0
2
Order By: Relevance
“…Other studies have also demonstrated that PCV vaccination of HIV-infected children is well tolerated [34]. The higher number of SAEs reported in HIV-infected children than in HIV-exposed children in study 034 was mainly due to a higher incidence of Table 8.…”
Section: Safety In At-risk Populationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Other studies have also demonstrated that PCV vaccination of HIV-infected children is well tolerated [34]. The higher number of SAEs reported in HIV-infected children than in HIV-exposed children in study 034 was mainly due to a higher incidence of Table 8.…”
Section: Safety In At-risk Populationsmentioning
confidence: 78%
“…Infants at higher risk of pneumococcal disease [33,34] were included in two studies of PHiD-CV completed by December 2012. Study 015/016 was an open controlled study conducted in Greece and Spain, in which 137 preterm infants and 149 term infants were enrolled to receive PHiD-CV coadministered with DTPa-HBV-IPV/Hib as primary vaccination at 2-4-6 months of age followed by a booster dose of PHiD-CV co-administered with DTPa-IPV/Hib at 16-18 months [28].…”
Section: Safety In At-risk Populationsmentioning
confidence: 99%
“…16 Other studies on earlier pneumococcal conjugate vaccines have also shown that subjects with higher CD4 counts have higher baseline antibody concentrations, and that baseline antibody concentrations strongly correlate with post-vaccination antibody concentrations. 17 This is presumably from a stronger immune response to prior pneumococcal exposure in subjects with higher CD4 counts. This would make sense in that CD4 cells are critical to the creation of germinal centers and the development of longlasting memory B cells, either from pneumococcal natural infection or PCV, that can be boosted though subsequent pneumococcal antigen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…34 A review of immunogenicity studies conducted in HIVinfected adults showed that response to conjugated vaccines was improved when vaccination was carried out in patients treated with antiretroviralsindependently of baseline CD4C cell count. 35 Regarding the 13-valent conjugate vaccine, clinical data are lacking. However satisfactory immunogenicity and safety data, including in patients previously vaccinated with the polysaccharide vaccine have been reported.…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%